Crackless transfer of large-area graphene films for superior-performance transparent electrodes. (March 2016) - Cai, Caoyuan; Jia, Feixiang; Li, Alei; Huang, Fan; Xu, Zhihao; Qiu, Longzhen; Chen, Yiqing; Fei, Guangtao; Wang, Min
Abstract: Graphene is a promising candidate as transparent electrode owing to its high optical transmittance and conductivity. Graphene transfer is still one of critical issues for achieving the high-performance transparent graphene electrodes. Here, we report a crackless transfer method without the removal of polymer, which is usually utilized as the carrier for graphene transfer. This method enables the successful transfer of single-layer graphene onto polymethyl-methacrylate (PMMA)/AB-glue/polyethylene-terephthalate (PET) up to 14-inch with a sheet resistance of 219 Ω sq −1 at 96.5% transmittance. The conductivity is comparable with that of the doped graphene films, and is 5 times higher than that of undoped graphene films obtained by the transfer with polymer removal. Our experiment results show that the sheet resistance is proportional to the area of graphene crack, which is unavoidably caused during removing the polymer carrier. So the high conductivity is attributed to crackless graphene films produced by our new transfer method.